Determination of Natural Radioactivity Level on Soil and Radiological Hazards in The Geotermal Area of Solok South, West Sumatera - Nurul Khaira Sabila; Dinda Nurul Syifa; Mohammad Randy Alhafiz; Sri Oktamuliani (Universitas Sebelas Maret, 2021)
Solok Selatan is one of the areas in West Sumatra that has geothermal potential, contains much higher levels of radioactive substances in the soil in the form of Radium (Ra-226), Thorium (Th-232), and Potassium (K-40). This study aimed to measure the concentration of Ra-226. Th-232, and K-40 contained in the soil in the Solok Selatan which was then reviewed based on PERKA BAPETEN No. 9 of 2009 and UNSCEAR 2000, also evaluates the average radium equivalent activity (Raeq), representative level index (Iyr), external hazard index (Hex). Soil samples were collected from seven different locations. The radionuclide activity concentration was measured by using a gamma spectrometer in the PTKMR BATAN laboratory, with the results of the average radionuclide measurement Ra-226 being 28.58 Bq/kg, Th-232 was 44.74 Bq/kg and K-40 at 323.29 Bq/kg. For the average value of Raeq is 118,051 Bq/kg, Iyr is 0.853 and Hex is 0.335. Based on BAPETEN PERKA No. 9 of 2009 and UNSCEAR 2000, the radionuclide activity concentration was found still within safe limits. It does not pose a health hazard to the people living in the area.